An energy efficient privacy-preserving content sharing scheme in mobile social networks. Issue 5 (October 2016) - He, Zaobo; Cai, Zhipeng; Han, Qilong; Tong, Weitian; Sun, Limin; Li, Yingshu
Abstract The rising popularity of mobile social media enables personalization of various content sharing and subscribing services. These two types of services entail serious privacy concerns not only to the confidentiality of shared content, but also to the privacy of end users such as their identities, interests and social relationships. Previous works established on the attribute-based encryption (ABE) can provide fine-grained access control of content. However, practical privacy-preserving content sharing in mobile social networks either incurs great risk of information leaking to unauthorized third parties or suffers from high energy consumption for decrypting privacy-preserving content. Motivated by these issues, this paper proposes a publish–subscribe system with secure proxy decryption (PSSPD) in mobile social networks. First, an effective self-contained privacy-preserving access control method is introduced to protect the confidentiality of the content and the credentials of users. This method is based on ciphertext-policy ABE and public-key encryption with keyword search. After that, a secure proxy decryption mechanism is proposed to reduce the heavy burdens of energy consumption on performing ciphertext decryption at end users. The experimental results demonstrate the efficiency and privacy preservation effectiveness of PSSPD.